2017
DOI: 10.1101/145664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteins with prion-like domains can form viscoelastic condensates that enable membrane remodeling and endocytosis

Abstract: SummaryEndocytosis underlies intra- and extracellular material trafficking in eukaryotes, and is essential to protein metabolism, intercellular signaling, membrane remodeling and other cell regulatory processes. Although endocytosis is usually driven by F-actin polymerization in yeast cells, membrane invagination can also occur through a yet unknown actin-independent mechanism when turgor pressure is relieved. Here, we demonstrate that membrane invagination can arise from liquid-liquid phase separation (demixi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 60 publications
1
34
0
1
Order By: Relevance
“…3C). The droplet's interfacial energy is favorable up to an invagination depth of~80 nm, close to the range that the CCP moves before scission (~100 nm) [110,140], totaling 1000 k B T [139]. However, the interfacial energy minimum is reached at an invagination depth of~40 nm, which falls short of the expected invagination depth [139].…”
Section: Liquid Phase Separationmentioning
confidence: 72%
See 1 more Smart Citation
“…3C). The droplet's interfacial energy is favorable up to an invagination depth of~80 nm, close to the range that the CCP moves before scission (~100 nm) [110,140], totaling 1000 k B T [139]. However, the interfacial energy minimum is reached at an invagination depth of~40 nm, which falls short of the expected invagination depth [139].…”
Section: Liquid Phase Separationmentioning
confidence: 72%
“…The droplet's interfacial energy is favorable up to an invagination depth of ~ 80 nm, close to the range that the CCP moves before scission (~ 100 nm) , totaling ~ 1000 k B T . However, the interfacial energy minimum is reached at an invagination depth of ~ 40 nm, which falls short of the expected invagination depth . Furthermore, it remains unclear exactly what causes, disrupts, maintains, or contributes to phase‐separated droplet formation within endocytic structures and it is especially difficult to experimentally probe the dynamic stability of droplets in endocytosis, given that the process is out of equilibrium and completed within seconds.…”
Section: Other Putative Mechanismsmentioning
confidence: 96%
“…In the case of Ede1, the coiled-coil and disordered domains are important for its phase separation properties. Many other endocytic proteins have unstructured (Dafforn and Smith, 2004;Kalthoff et al, 2002) and prion-like (Alberti et al, 2009) regions that may have a tendency to phase separate, and recent studies suggested that the unstructured protein regions can generate force for membrane bending during vesicle budding (Bergeron-Sandoval et al, 2018;Busch et al, 2015;Snead et al, 2017).…”
Section: Other Roles For Phase Separation In Endocytosismentioning
confidence: 99%
“…Whereas these long-known, floating droplet or-ganelles are large enough to be visible using simpler light microscopic techniques, in the past years liquid-liquid phase separation has been implicated in multifarious processes in which – often sub-micrometer-sized – condensates are formed at particular sites in the cell: at sites of DNA repair foci (Altmeyer et al, 2015), Polycomb-mediated chromatin silencing (Tatavosian et al, 2019), transmembrane signalling (Banjade and Rosen, 2014; Case et al, 2019), microtubule formation (So et al, 2019; Huang et al, 2018; Hernández-Vega et al, 2017; Jiang et al, 2015), actin polymerization (Weirich et al, 2017), endocytosis (Bergeron-Sandoval et al, 2017; Miao et al, 2018), transcription (Cho et al, 2018; Sabari et al, 2018; Chong et al, 2018; Boehning et al, 2018), at presynaptic active zones (Wu et al, 2019; Zeng et al, 2018), and for RNP transport (Formicola et al, 2019; Alami et al, 2014). Such localized condensates form upon a local stimulus to recruit the required set of proteins and are dissolved once the job is done.…”
mentioning
confidence: 99%